1984
DOI: 10.1104/pp.74.3.701
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Nitrogenase Regulation by Ammonium and Methylamine and the Effect of MSX on Ammonium Transport in Anabaena flos-aquae

Abstract: Ammonium suppresses nitrogenase activity in Anabaena flos-aquae (Lyng) Breb. at all pH values tested. L-Methionine-DL-sulfoximine at 1 millimolar totally inhibited glutamine synthetase, and 10 micromolar partially inhibited. Both concentrations protected nitrogenase activity from ammonium-induced suppression at pH 7.1 and 8.1. At pH 93 and 10.2, methionine sulfoximine did not alleviate the suppression of nitrogenase by ammonium. This pH-dependent protection of nitrogenase activity is a result of the noncompeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
30
1

Year Published

1985
1985
2000
2000

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 11 publications
5
30
1
Order By: Relevance
“…This contrasts with the report of a direct inhibition of NH4+ transport system by MSX in Anabaenaflos-aquae (12). It has recently been pointed out (3) that methylammonium is metabolized to methylglutamine in cyanobacteria.…”
contrasting
confidence: 52%
“…This contrasts with the report of a direct inhibition of NH4+ transport system by MSX in Anabaenaflos-aquae (12). It has recently been pointed out (3) that methylammonium is metabolized to methylglutamine in cyanobacteria.…”
contrasting
confidence: 52%
“…This increase in N content in the grain with inoculation without N was markedly higher than in the treatments that received additional N, probably due to higher N uptake after anthesis (Table 4). Such increment was above 66%, representing about 8.4 kg ha -1 of N. This effect was not observed in the treatments receiving N fertilizer, which could be attributed to the inhibitory effect of N compounds on the nitrogenase activity of the bacterium (Turpin et al, 1984). In this regard, Zimmer et al (1988) com-mented that the growth of the bacterium with nitrite or nitrate suppresses the biosynthesis of nitrogenase, since the cells synthetize nitrite reductase and nitrate reductase instead of using their limited energy in the nitrogenase reaction.…”
Section: Fig 2 Effect Of Wheat (T Aestivum L Cv Br 23) Inoculatmentioning
confidence: 84%
“…The initial rapid phase may relate to the transport mechanism itself, while the second slower phase may relate to the metabolic transformation of MA to g-methylglutamine by glutamine synthetase (GS). In studies with cyanobacteria (Boussiba et al 1984;Turpin et al 1984;Kerby et al 1986), the second phase can be eliminated with the GS inhibitor methionine sulfoximine (MSX). In other studies that have demonstrated the biphasic nature of MA uptake in the dinoflagellate Gonyaulux (Balch 1986) and the diatom Phaeodactylum (Wright and Syrett 1983), the second phase was not related to the metabolism of MA.…”
Section: Discussionmentioning
confidence: 99%
“…Hackette et al 1970), free-living and symbiotic bacteria (Kleiner and Fitzke 198 1;Wiegel and Kleiner 1982), cyanobacteria (Turpin et al 1984), microalgae (Wheeler 1980), macroalgae (Wheeler 1979;MacFarlane and Smith 1982), lichens with algal endosymbionts (Tapper 1983), and angiosperms (Smith 1982). With few exceptions, [14C]MA has proved useful in understanding NH,+ transport, and generally the "affinity" of the transport system has been shown to be greater (i.e.…”
mentioning
confidence: 99%